2022
DOI: 10.1111/vop.12973
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive optical coherence tomography angiography: A comparison with fluorescein and indocyanine green angiography in normal adult dogs and cats

Abstract: While the retinal vasculature can be assessed by simple funduscopy, a more detailed assessment can be performed by conventional angiography using dyes such as fluorescein or indocyanine green. The development of optical coherence tomography angiography (OCT-A) allows a non-invasive detailed examination of posterior segment vasculature. The purpose of this prospective study was to compare imaging of posterior segment vasculature in normal dogs and cats using OCT-A, fluorescein angiography (FA), and indocyanine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…12 In veterinary medicine, fluorescein sodium has also been used for angiography, and one report described the use of intravenous fluorescein sodium injection to guide the resection of intracranial lesions in 22 dogs. [13][14][15][16] Fluorescein sodium fluorescence microscope-integrated lymphangiography has been reported in human medicine once in 2015. The goal of the case report was to assess the lymphatic drainage pathway and patency in a patient treated for secondary lymphedema by lymphaticovenular anastomoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In veterinary medicine, fluorescein sodium has also been used for angiography, and one report described the use of intravenous fluorescein sodium injection to guide the resection of intracranial lesions in 22 dogs. [13][14][15][16] Fluorescein sodium fluorescence microscope-integrated lymphangiography has been reported in human medicine once in 2015. The goal of the case report was to assess the lymphatic drainage pathway and patency in a patient treated for secondary lymphedema by lymphaticovenular anastomoses.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescein sodium has also been used to localise multiple muscular ventricular septal defects during open heart surgery and to confirm the presence of any residual defects 12 . In veterinary medicine, fluorescein sodium has also been used for angiography, and one report described the use of intravenous fluorescein sodium injection to guide the resection of intracranial lesions in 22 dogs 13–16 …”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Recently, it has been published that outer retinal band and choriocapillaris can be identified in healthy dogs and cats, 19 and different vascular layers of the retina and choroid are nicely evaluated by OCT-A in cats. 20 The present report describes the clinical case of bilateral corneal dermoids associated with bilateral choroidoscleral colobomas in a cat, its SD-OCT fundus evaluation, the surgical outcome and the follow-up of lesions up to 18 months. A review of literature suggests that it is the first case reported of such an association in a domestic cat.…”
Section: Introductionmentioning
confidence: 94%
“…Several studies have shown that spectral domain OCT (SD‐OCT) is a reliable method to evaluate different retinal layers and optic nerve morphology in colobomas in dogs, 15 in healthy or glaucomatous cats 16–18 . Recently, it has been published that outer retinal band and choriocapillaris can be identified in healthy dogs and cats, 19 and different vascular layers of the retina and choroid are nicely evaluated by OCT‐A in cats 20 …”
Section: Introductionmentioning
confidence: 99%